Sclerosis of the mammary arteries in perimenopausal women as an early marker of atherosclerosis - А. В. Гурандо; О. О. Єфіменко; І. М. Ретунська (Publishing House TRILIST, 2019)
Purpose of the study. To assess the sclerosis of mammary arteries (SMA) frequency depending on the age and duration of menopause by conducting mammography in the studied women of perimenopausal age. Materials and methods. To examine the morphological and functional state of the mammary gland was performed a clinical examination of the mammary glands which included examination, palpation, and bilateral mammography. Together with the assessment of the state of the mammary gland, mammary arteries were evaluated for their sclerosis. The severity of menopausal syndrome was assessed using the Menopausal Rating Scale. 584 women were examined with ultrasound and divided into groups: Group I - women 40-45 years aged and Group II - women 46-51 years aged. Results of the study. SMA was more common in older women - 3.7% in Group I compared with 8.4% in Group II (p <0.05). Certain patterns have also been identified between the SMA incidence and the menopausal symptoms presence. Incidence of SMA was greater in both younger and older women with manifestations of menopausal syndrome than in women without manifestations of menopausal syndrome. The study identified additional risk factors for the SMA development as an early marker of atherosclerosis, among which is duration of menopause, severity of menopausal syndrome, presence of concomitant breast pathology, overweight and a positive family history of atherosclerosis. Conclusions. SMA identification during mammography is an important additional advantage of examining women and requires mandatory cardiac support and the introduction of prophylactic agents for cardiovascular pathology. Authors' data confirm the importance of an interdisciplinary approach and the benefits of using modern methods for diagnosing and preventing diseases during the perimenopause period in order to improve the quality and longevity of women.